The Digitalization Impact of The Payment System Through Qris on East Java Regional Financial Transactions - Prilyandari Dina Saputri (East Java Economic Journal, 2023)
Payment system transaction efficiency can be optimized by utilizing technology in the digital era. Bank Indonesia with the Indonesian Payment System Association (ASPI) launched QRIS as a payment transaction instrument employing a standardized QR code. This study aims to evaluate the impact of the QRIS implementation policy and the QRIS transaction limit change policy on financial transactions in East Java Province. Financial transactions are represented using outflows, which is the cash flow of currency going out from Bank Indonesia. The research was performed using the intervention analysis. The results show that the implementation of QRIS in January 2020 had a significant impact on reducing outflow 5 periods after the policy was implemented. The decline in outflows even exceeds 90% in 2021 and exceeds 80% in 2022. The QRIS transaction limit change policy does not affect the increase/decrease in outflow transactions. This can be caused by QRIS users who are dominated by the MSME sector so the transactions made are retail. Further research on the impact of the QRIS policy using the amount of money in circulation, the net flow of currency, and digital banking transactions as the indicator of financial transactions also need to be carried out.